Eksplorasi Perilaku Manajemen Kebersihan Menstruasi Dan Faktor Yang Mempengaruhi Pada Narapidana Di Lapas Perempuan Padang - FEBRIANI, TITA (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background: Poor Menstrual Hygiene Management (MHM) can adversely affect women’s reproductive health, particularly for incarcerated individuals. Addressing the MHM needs of women in prison is crucial to ensure adequate hygiene access, safeguarding their health and well-being despite confinement. Purpose: This study aimed to explores the behaviors and factors influencing MHM practices among female inmates in correctional settings.Method: Employing a qualitative phenomenological approach, the research was conducted from June to August 2024. Ten informants were purposively selected from the Class IIB Women’s Prison in Padang. Data were gathered through in-depth interviews, observations, and document reviews, then analyzed using Interpretative Phenomenological Analysis (IPA).Result: The study's findings revealed two main themes. The first theme was the poor MHM practices among inmates, and the second theme identified the factors influencing their MHM practices, which comprised three categories: limited availability of facilities, lack of MHM-related information, and support from family and friends. Conclusion: The study concluded that the limited availability of facilities was the primary barrier to maintaining menstrual hygiene in correctional facility.